Іmproving the methodological framework software investments in tourism (Journal of Economic Research & Business Administration, 2015)
The article considers the methodological issues and providing of investments in Republic. The mechanism of investments allocation across the sectors in analyzed/ the article contains recommendations importing the effectiveness in tourism industry. Policy of development of tourism in the Azerbaijan Republic it is directed on its transformation soon in one of priority branches of national economy. It found the reflection in the accepted state program, and also in the actions which are carried out at the state level. With the same purpose in certain regions of the republic for development of various forms of tourism the network infrastructure meeting the international requirements was created. For strengthening of a role of tourism in national economy legal, organizational and economic issues have to be resolved, in a root causing its priority external and internal investment providing has to be improved.
Keywords: Ecotourism; agrotourism; development of various forms of tourism; tourist branches